The Influence of Pore Solutions Properties on Drying in Cementitious Materials. Issue 2 (18th October 2013) - Villani, Chiara; Spragg, Robert; Pour‐Ghaz, Mohammad; Jason Weiss, W.; Sanchez, F.
<x xml:space="preserve">Abstract</x> The drying of cementitious materials can be influenced by the properties of the fluid in the pores. While there are numerous studies on drying, very few explicitly focus on the properties of the pore fluid. This work investigates the influence of deicing salts on the properties of the pore fluid. The change that deicing salts cause in surface tension and viscosity is described in this study as a function of concentration and temperature. As a relatively limited number of measurements have been reported in literature, it can be difficult to describe the properties over a wide range of concentrations or temperatures. To overcome this limitation, this work provides measurements over concentration and temperature ranges. Semiempirical relationships were successfully fitted to the data confirming the possibility to predict viscosity and surface tension changes with temperature and salt concentration. The implications of the fluid properties on the drying behavior are also discussed as they relate to the diffusion coefficient. The models applied effectively predict the initiation of drying. Further improvements are however necessary to describe the diffusion coefficient as function of the degree of saturation in the presence of deicing salts which appear to be needed to account for the chemical interaction between the matrix and the fluid.